Hours of Paid Work Among Single and Partnered Mothers in Australia: The Role of Child Care Packages. (February 2016) - Brady, Michelle; Perales, Francisco
Research has established that families in developed countries commonly combine multiple sources of child care. Yet, families' packages of child care and their effect on maternal labor force participation are underresearched, and the few existing empirical studies are primarily descriptive or use cross-sectional data. We add to the existing literature by theorizing and testing the relationships between family type, child care arrangements, and mothers' work hours using Australian panel data and panel regression models. We find that employed mothers of young children who use a mixed child care package complete more hours of paid work than do employed mothers of young children who use other child care packages, but the reasons for this association are different among single and partnered mothers. For single mothers the most important characteristic of mixed child care packages appears to be their flexibility, whereas for partnered mothers mixed child care increases employment hours by maximizing the hours of child care available to them.